A PA / PPE composite material and its preparation method and application
By using magnesium hydroxide nanosheets of specific sizes in PA/PPE composites, the problem that existing materials are difficult to achieve ideal CTI performance is solved, and the level 0 CTI level and excellent flame retardant effect are achieved, while maintaining the advantages of mechanical properties and appearance performance.
Patent Information
- Application Number
- CN202311807882.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-12-26
AI Technical Summary
It is difficult for existing PA/PPE composite materials to achieve ideal CTI performance, especially black products cannot reach the level 0 CTI level. At the same time, in the process of improving CTI performance, mechanical performance and appearance performance are difficult to guarantee.
By introducing specific magnesium hydroxide nanosheets as modified components into the PA/PPE composite material, the average particle size is 3 to 5 μm and the average thickness is 0.05 to 0.08 μm, the level 0 CTI level can be achieved at a low introduction amount, while maintaining excellent flame retardant effect and mechanical properties.
It has achieved that the CTI performance of PA/PPE composite materials is improved to level 0 under a low addition amount, and the flame retardant effect is excellent, the mechanical properties are comparable to those of the existing products, and the appearance performance of the products can be guaranteed.
Smart Images

Figure BDA0004630781740000071 
Figure BDA0004630781740000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer alloy materials, and in particular to a PA / PPE composite material and a preparation method and application thereof. Background Art
[0002] PPE resin (polyphenylene ether resin) has excellent heat resistance, solvent resistance, water resistance, etc., and theoretically has more prospects than other types of plastic materials, but its processing performance is poor. In addition, since PPE resin has high carbonization and is flame-retardant and self-extinguishing, it will form flashover discharge at a voltage of 300V, and then generate carbides on the surface and form a conductive path, which ultimately makes the actual CTI performance of PPE resin poor.
[0003] Therefore, people use PA resin (polyamide resin) and PPE resin to blend, taking advantage of the poor carbonization and excellent processing properties of PA resin to achieve performance complementarity with PPE resin. However, the existing PA / PPE composite materials still have difficulty in achieving ideal CTI performance, especially for black products, the existing products have no way to reach the 0-level CTI level; on the other hand, PA resin is mostly used in the field of edge protection, so the appearance of the product must be guaranteed. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a PA / PPE composite material, which uses specific magnesium hydroxide nanosheets as a modified component to achieve a CTI level of Class 0 at a relatively low introduction amount, and has excellent flame retardant effect, and the mechanical properties are not significantly different from those of existing conventional products.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A PA / PPE composite material comprises the following components in parts by weight:
[0007] 25-40 parts of polyamide resin, 8-32 parts of polyphenylene ether resin, 4-8 parts of compatibilizer, 7-15 parts of flame retardant, 5-12 parts of magnesium hydroxide nanosheets;
[0008] The average particle size of the magnesium hydroxide nanosheets is 3 to 5 μm, and the average thickness is 0.05 to 0.08 μm.
[0009] Preferably, the PA / PPE composite material comprises the following components in parts by weight:
[0010] 28-35 parts of polyamide resin, 10-28 parts of polyphenylene ether resin, 5-7 parts of compatibilizer, 8-13 parts of flame retardant, and 6-10 parts of magnesium hydroxide nanosheets.
[0011] In some conventional PPE composite materials, some inorganic hydroxides such as magnesium hydroxide and aluminum hydroxide are also used to improve the CTI performance of the product, but the final improvement is not ideal. At the same time, for some non-black color products, although increasing the amount of inorganic hydroxide added can improve the CTI performance of the product to the expected value, at the same time, since the substance is essentially a powder filler, it will also cause the mechanical properties of the product to be significantly reduced. In the technical solution of the present invention, the inventor selects magnesium hydroxide nanosheets of this specific size structure as a modifying component. Compared with magnesium hydroxide nanosheets of other sizes and other types of magnesium hydroxide and inorganic hydroxides, the CTI level of the product can be significantly improved to level 0 with a relatively small addition amount relative to the composite matrix resin, and the flame retardant and mechanical properties of the product will not be significantly affected. The mechanical properties of the product are comparable to those of the composite material prepared by the conventional magnesium hydroxide modifier, so it can be completely replaced.
[0012] In addition, the inventors found that the introduction of the magnesium hydroxide nanosheets of the present invention not only improves the CTI performance of the product, but also ensures the appearance performance of the product, while conventional inorganic hydroxides as modifiers cannot achieve the same performance level at the same addition amount.
[0013] It should be noted that the method for testing the particle size and thickness of the magnesium hydroxide nanosheets of the present invention is to directly observe and test using a scanning electron microscope after calcining the product and separating the glass fibers and other impurities in the ash obtained, and the number of tested particles is ≥10.
[0014] Preferably, the sum of the mass contents of the PA resin and the PPE resin in the PA / PPE composite material is not less than 50 wt%.
[0015] Preferably, the PA / PPE composite material also includes 0.01 to 0.8 parts of colorant.
[0016] In the PA / PPE composite material of the present invention, due to the effect of specific magnesium hydroxide nanosheets, the product can still maintain the expected CTI level when introducing colorants of different color systems (different color systems will cause different performance results of the composite resin during the CTI test process). Therefore, the product can be designed into plastic products of different colors according to actual needs and has a wide range of applications.
[0017] Preferably, the colorant is an organic colorant.
[0018] More preferably, the colorant is a black colorant.
[0019] More preferably, the colorant is at least one of dye black and aniline black.
[0020] More preferably, the colorant is aniline black.
[0021] According to the inventor's experiments, some non-black PA / PPE composite materials can achieve a CTI level of 0 by introducing a large amount of inorganic hydroxide (such as conventional magnesium hydroxide powder) without considering the mechanical properties. However, for black system products, even if a sufficient amount of conventional modified components are introduced, the standard cannot be met. However, the product of the present invention can achieve similar comprehensive performance effects to other colors even if black colorants are introduced under specific system components.
[0022] Preferably, the mass ratio of the polyamide resin to the polyphenylene ether resin is (0.8-3.1):1.
[0023] More preferably, the mass ratio of the polyamide resin to the polyphenylene ether resin is (0.83-2):1.
[0024] The magnesium hydroxide nanosheets of the present invention have slightly lower strength and relatively thinner size than conventional functional fillers or ordinary magnesium hydroxide powders. When the proportion of the matrix resin is maintained within the above range, the CTI performance of the product is effectively improved, and the flame retardant performance of the product can also be maintained at a relatively good level.
[0025] Preferably, the polyamide resin is at least one of PA6 resin, PA66 resin, PA46 resin, PA6T resin, PA9T resin and PA10T resin.
[0026] Preferably, the relative viscosity of the polyamide resin is 2 to 3.4 under the test condition of 25° C. sulfuric acid solution according to GB / T 12006.1-2009.
[0027] More preferably, the relative viscosity of the polyamide resin is 2.3 to 3.2 under the test condition of 25° C. sulfuric acid solution according to GB / T 12006.1-2009.
[0028] More preferably, the relative viscosity of the polyamide resin is 2.4 to 2.8 under the test condition of 25° C. sulfuric acid solution according to GB / T 12006.1-2009.
[0029] Preferably, the polyphenylene ether resin has a melt mass flow rate of 2 to 25 g / 10 min under the test conditions of 280° C. and 5 kg according to GB / T 3682-2000.
[0030] More preferably, the polyphenylene ether resin has a melt mass flow rate of 5 to 20 g / 10 min under the test conditions of 280° C. and 5 kg according to GB / T 3682-2000.
[0031] More preferably, the polyphenylene ether resin has a melt mass flow rate of 8 to 12 g / 10 min under the test conditions of 280° C. and 5 kg according to GB / T 3682-2000.
[0032] Preferably, the compatibilizer is at least one of maleic anhydride grafted SEBS, maleic anhydride grafted POE, and maleic anhydride grafted PPE.
[0033] Preferably, the compatibilizer is a maleic anhydride graft, and the grafting rate of the compatibilizer is 0.5-2%.
[0034] More preferably, the compatibilizer is maleic anhydride grafted SEBS, and the grafting rate is 0.9-1.2%.
[0035] Preferably, the flame retardant is at least one of a phosphorus-based flame retardant and a phosphorus-nitrogen-based flame retardant.
[0036] More preferably, the flame retardant is a phosphorus-based flame retardant.
[0037] More preferably, the phosphorus-based flame retardant is red phosphorus.
[0038] More preferably, the phosphorus-based flame retardant can be added in the manner disclosed in the prior art, for example, in the form of microcapsule-coated masterbatch, in the form of inert resin-coated masterbatch, under highly protective atmosphere processing conditions, or under weak shear mode conditions. Any method can be implemented as long as it can ensure that the phosphorus-based flame retardant can exert the expected flame retardant effect under the processing or environmental conditions.
[0039] More preferably, the flame retardant is a phosphorus-based flame retardant added in the form of microcapsule-coated masterbatch, and the phosphorus content is 40 to 60 wt%.
[0040] Preferably, the PA / PPE composite material further comprises 15 to 30 parts of glass fiber.
[0041] Preferably, the glass fibers have an average diameter of 1 to 20 μm and an average length of 1 to 10 mm.
[0042] More preferably, the glass fibers have an average diameter of 8 to 12 μm and an average length of 2 to 4 mm.
[0043] More preferably, the average diameter of the glass fiber is within the range of any one or both of 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 15 μm and 20 μm.
[0044] It should be noted that, without compromising the technical effects of the PA / PPE composite material of the present invention, the components of the product of the present invention may also include conventional additives such as lubricants, defoamers, antistatic agents, antioxidants, etc. The technical solution of the present invention does not specifically limit the PA / PPE composite material to an exclusive formula consisting of PA resin, polyphenylene ether resin, compatibilizer, flame retardant, glass fiber, magnesium hydroxide nanosheets and colorant.
[0045] Another object of the present invention is to provide a method for preparing the PA / PPE composite material, comprising the following steps:
[0046] The components except the glass fiber are mixed uniformly, and then the obtained mixture and the glass fiber are melted and granulated to obtain the PA / PPE composite material.
[0047] The preparation method of the PA / PPE composite material of the present invention has simple operation steps and can realize industrial large-scale production.
[0048] Preferably, the mixing speed is 1000-2000 rpm.
[0049] Preferably, the melting is carried out in a twin-screw extruder, and the temperature of each zone in the twin-screw extruder is set to: zone one temperature 210-230°C, zone two temperature 230-250°C, zone three temperature 240-260°C, zone four temperature 250-270°C, zone five temperature 250-270°C, zone six temperature 250-270°C, zone seven temperature 250-270°C, zone eight temperature 240-260°C, zone nine temperature 230-250°C, zone ten temperature 190-210°C, and the screw speed of the twin-screw extruder is 330-360rpm.
[0050] Another object of the present invention is to provide application of the PA / PPE composite material in the preparation of insulating flame-retardant plastic products.
[0051] The product of the present invention has excellent flame retardant effect and can achieve a CTI level of 0. It is the first PA / PPE composite material in the industry to be developed to this level. It also has mechanical properties comparable to existing products. Therefore, it can completely replace existing products and be applied to some plastic products with high requirements for insulation and flame retardant properties.
[0052] The beneficial effect of the present invention is that the present invention provides a PA / PPE composite material, which uses specific magnesium hydroxide nanosheets as a modified component, can achieve a CTI level of Class 0 with a relatively low introduction amount, and at the same time has excellent flame retardant effect, and the mechanical properties are not significantly different from those of existing conventional products. DETAILED DESCRIPTION
[0053] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0054] Examples 1 to 10
[0055] The PA / PPE composite material and the preparation method and application examples of the present invention, the components of the PA / PPE composite material are shown in Table 1.
[0056] The preparation method of the PA / PPE composite material comprises the following steps:
[0057] The components except the glass fiber were mixed uniformly for 2 minutes, and then the obtained mixture and the glass fiber (added from the side feeding port) were melted and granulated to obtain the PA / PPE composite material.
[0058] The mixing speed was 1500 rpm.
[0059] The melting is carried out in a twin-screw extruder, and the temperature of each zone in the twin-screw extruder is set to: zone one temperature 215-225°C, zone two temperature 235-245°C, zone three temperature 245-255°C, zone four temperature 255-265°C, zone five temperature 255-265°C, zone six temperature 255-265°C, zone seven temperature 255-265°C, zone eight temperature 245-255°C, zone nine temperature 235-245°C, zone ten temperature 195-205°C, and the screw speed of the twin-screw extruder is 340rpm.
[0060] Comparative Examples 1 to 7
[0061] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0062] Among the components described in each embodiment and comparative example,
[0063] The polyamide resin 1 is M2400 (PA6) produced by Xinhui Meida, and the relative viscosity is 2.4 under the test condition of 25°C sulfuric acid solution according to GB / T12006.1-2009;
[0064] The polyamide resin 2 is EP-158 (PA66) produced by Huafeng, and the relative viscosity is 2.6 under the test condition of 25°C sulfuric acid solution according to GB / T12006.1-2009;
[0065] The polyphenylene ether resin 1 is LXR035 (poly (2,6-dimethyl-1,4-phenylene) ether) produced by Shanxi Bluestar, and according to GB / T 3682-2000, the melt mass flow rate under the test conditions of 280°C and 5kg is 12g / 10min;
[0066] The polyphenylene ether resin 2 is LXR040 (poly (2,6-dimethyl-1,4-phenylene) ether) produced by Shanxi Bluestar, and the melt mass flow rate under the test conditions of 280° C. and 5 kg is 8 g / 10 min;
[0067] The flame retardant 1 is a microcapsule-coated red phosphorus masterbatch, brand FR9950T, red phosphorus content of 50wt%, Tongcheng Xinde Co., Ltd.
[0068] The magnesium hydroxide nanosheet 1 is 10A produced by Kyowa of Japan, with an average particle size of 4 μm and an average thickness of 0.06 μm;
[0069] The magnesium hydroxide nanosheets 2 are LY1-S produced by Kyowa of Japan, with an average particle size of 0.9 μm and an average thickness of 0.2 μm;
[0070] The magnesium hydroxide nanosheets 3 are LY1-X produced by Kyowa of Japan, with an average particle size of 3 μm and an average thickness of 0.5 μm;
[0071] The magnesium hydroxide powder is 2500-G produced by Yingkou Huanqiu Powder, with a particle size of D 50 3.5μm;
[0072] The glass fiber is ECS10-03-568H produced by Jushi Group, with an average diameter of 10 μm and an average length of 3 mm;
[0073] The compatibilizer 1 is SEBS FG 1901 produced by Kraton, USA, maleic anhydride grafted SEBS, and the grafting rate is 1%;
[0074] The compatibilizer 2 is FUSABOND N493 produced by DuPont, USA, maleic anhydride grafted POE, and the grafting rate of FUSABONDN493 is 0.4%;
[0075] The compatibilizer 3 is SH024 produced by Dongguan Shenghao Plastic Co., Ltd., maleic anhydride grafted PPO, SH024, the grafting rate is 2%;
[0076] The colorant 1 is commercially available aniline black;
[0077] The colorant 2 is a commercially available dye black;
[0078] The colorant 3 is commercially available cobalt green;
[0079] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0080] Table 1
[0081]
[0082] Table 2
[0083] Component weight Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Polyamide resin 1 30 30 30 30 30 30 30 Polyphenylene ether resin 1 25 25 25 25 25 25 25 Fiberglass 20 20 20 20 20 20 20 Flame retardant 1 10 10 10 10 10 10 10 Magnesium hydroxide nanosheets 1 3 18 Magnesium hydroxide nanosheets 2 8 Magnesium hydroxide nanosheets 3 8 Magnesium hydroxide powder 8 10 20 Compatibilizer 1 6 6 6 6 6 6 6 Pigment 1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Average particle size of magnesium hydroxide nanosheets in the product (μm) 4.2 3.9 0.92 3.1 3.5 3.6 3.5 Average thickness of magnesium hydroxide nanosheets in the product (μm) 0.05 0.06 0.18 0.52 / / /
[0084] Effect Example 1
[0085] In order to verify the performance of the PA / PPE composite material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0086] (1) CTI performance test: According to GB / T 4207-2022, a tracking test is conducted. A certain voltage is applied between two electrodes. A drop of standard electrolyte solution is dripped on the surface of the insulating material every 30 seconds. This patent uses 0.1% ammonium chloride solution until the sample withstands 50 drops of solution or the sample is damaged. A lower or higher voltage is applied to other test points of the sample and the test is conducted again until the highest voltage value at which 50 drops of solution do not cause damage is obtained at 5 different test points: this is the CTI value. When the highest CTI voltage value is greater than 600V, it is CTI level 0.
[0087] (2) Appearance: Injection molded color plates (84*54*2.0mm) are inspected for any rust on the surface of the plates. The rust is then evaluated based on the rust on the surface of the plates. The rust is divided into four levels: no rust, inconspicuous rust (the rust is less than 5% and is shallow, which does not affect the appearance of the plate), obvious rust (the rust is 5-20% and can only maintain a good appearance), and more rust (the rust is greater than 20% and has significantly affected the appearance of the plate).
[0088] (3) Mechanical properties test: Flexural modulus: tested in accordance with ISO 178:2001 standard; Impact strength: tested in accordance with ISO 180:2000 standard, notch type is IZOD A type notch;
[0089] The test results are shown in Tables 3 and 4.
[0090] Table 3
[0091]
[0092] Table 4
[0093] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 CTI 375V >600V 520V 425V 375V 425V 475V <![CDATA[Impact strength (KJ / m 2 )]]> 8.4 4.2 8.5 9.5 8.2 7.6 5.4 Flexural modulus (MPa) 6600 6150 6110 6270 6540 6450 6150 Appearance The flower is not obvious The flower is not obvious The flower is not obvious The flower is not obvious The material flower is obvious The material flower is obvious The material flower is obvious
[0094] It can be seen from Table 3 and Table 4 that the PA / PPE composite material of the present invention has excellent comprehensive performance. Each product can reach the CTI level of 0, and the impact performance can be maintained at 5KJ / m 2 More than; in addition, the flexural modulus of the product can be maintained above 6000MPa, which meets the basic mechanical use requirements, and the appearance of the product is basically not obvious. It can be seen from Examples 9 and 10 that the PA / PPE composite material of the present invention is not limited to a single color system. When the black system, which is the most difficult to achieve the expected effect, can also achieve the ideal level, other color systems or products without introducing colorants can also obtain excellent comprehensive performance. It can be seen from Example 4 compared with Example 7 and Example 8 that, under the premise of using a specific magnesium hydroxide nanosheet as a CTI level modifying component, based on its special configuration, the use of maleic anhydride grafted SEBS as a compatibilizer can enable it and glass fiber to achieve good dispersion and uniformity in the PA / PPE composite resin system, and the mechanical properties of the final product are better. It can be seen from Comparative Example 1, Examples 3 to 5 and Comparative Example 2 that when too little magnesium hydroxide nanosheet is introduced, the CTI level of the product is poor, and as the content of this component gradually increases, the CTI level of the product reaches level 0; but if this component is added too much, the impact performance of the product is greatly reduced, so it is necessary to maintain its addition amount at 5 to 12 parts. According to Comparative Examples 3 to 4, it can be seen that magnesium hydroxide nanosheets of not any size can achieve the expected CTI performance improvement in the black PA / PPE composite material system. For ordinary magnesium hydroxide powder, as shown in Comparative Examples 5 to 7, although the CTI performance of the product will be improved under the condition of large content introduction, it still cannot reach the 0-level CTI level, and the appearance performance of the product cannot be improved. Similarly, the inventors found through experiments that the products of Comparative Examples 3 to 4 cannot reach the level of the example products after the introduction of magnesium hydroxide nanosheets 2 or magnesium hydroxide nanosheets 3, indicating that the component needs to be maintained at a specific size to work effectively.
[0095] In addition, the flame retardancy test of each embodiment product was carried out according to UL94, and the results were all V-0, indicating that each product has good flame retardancy.
[0096] Effect Example 2
[0097] In order to explore the effect of the ratio of polyamide resin and polyphenylene ether resin in the product of the present invention on the product performance, control groups 1 to 6 were set up, and the formulas were shown in Table 5. The products were prepared according to the embodiment method, and the CTI performance test was carried out according to the method described in Example 1. At the same time, the appearance and flame retardant grade tests were carried out, and the appearance test was the same as that in Example 1.
[0098] The results are shown in Table 6.
[0099] Table 5
[0100] Component weight Control group 1 Control group 2 Control group 3 Example 4 Control group 4 Control group 5 Control group 6 Polyamide resin 1 10 20 25 30 35 40 55 Polyphenylene ether resin 1 45 35 30 25 20 15 0 Flame retardants 10 10 10 10 10 10 10 Fiberglass 20 20 20 20 20 20 20 Magnesium hydroxide nanosheets 1 8 8 8 8 8 8 8 Compatibilizer 1 6 6 6 6 6 6 6 Pigment 1 0.5 0.5 0.5 0.5 0.5 0.5 0.5
[0101] Table 6
[0102] Test items Control group 1 Control group 2 Control group 3 Example 4 Control group 4 Control group 5 Control group 6 CTI 400V 575V >600V >600V >600V >600V >600V Appearance More flowers The material flower is obvious The flower is not obvious The flower is not obvious The flower is not obvious The flower is not obvious The flower is not obvious Flame retardant grade V-0 V-0 V-0 V-0 V-0 V-1 NA
[0103] It can be seen from Table 6 that when the total addition amount of polyamide resin and polyphenylene ether resin remains unchanged but the addition ratio changes, the performance of the product will also change. When the polyamide in the product is less, the product not only has poor CTI performance, but also has obvious appearance defects. As the polyamide resin increases, the flame retardancy of the product begins to decrease. When the ratio of the two is maintained in the range of (0.8-2):1, the product not only has ideal flame retardancy and CTI performance, but also has good flame retardancy, can reach V-0 grade, good appearance, and is more practical. If the matching ratio exceeds the specified range of the present invention, the CTI performance or dimensional stability of the product will be greatly reduced.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PA / PPE composite material, characterized in that: The composition comprises the following components in parts by weight: 25-40 parts of polyamide resin, 8-32 parts of polyphenylene ether resin, 4-8 parts of compatibilizer, 7-15 parts of flame retardant, 5-12 parts of magnesium hydroxide nanosheets; The mass ratio of the polyamide resin to the polyphenylene ether resin is (0.8-3.1):1; The average particle size of the magnesium hydroxide nanosheets is 3-5 μm, and the average thickness is 0.05-0.08 μm; the compatibilizer is at least one of maleic anhydride grafted SEBS, maleic anhydride grafted POE, and maleic anhydride grafted PPE.
2. The PA / PPE composite material according to claim 1, characterized in that: The components of the PA / PPE composite material also include 0.01 to 0.8 parts of a colorant; the colorant is at least one of dye black and aniline black.
3. The PA / PPE composite material according to claim 1, characterized in that: The relative viscosity of the polyamide resin is 2 to 3.4 under the test condition of 25° C. sulfuric acid solution according to GB / T 12006.1-2009.
4. The PA / PPE composite material according to claim 1, characterized in that: The polyphenylene ether resin has a melt mass flow rate of 2 to 25 g / 10 min under the test conditions of 280° C. and 5 kg according to GB / T 3682-2000.
5. The PA / PPE composite material according to claim 1, characterized in that: The flame retardant is at least one of a phosphorus-based flame retardant and a phosphorus-nitrogen-based flame retardant.
6. The PA / PPE composite material according to claim 1, characterized in that: The PA / PPE composite material also includes 8 to 32 parts of glass fibers, wherein the average diameter of the glass fibers is 1 to 20 μm and the average length is 1 to 10 mm.
7. The method for preparing the PA / PPE composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components except the glass fiber are mixed uniformly, and then the obtained mixture and the glass fiber are melted and granulated to obtain the PA / PPE composite material.
8. Use of the PA / PPE composite material according to any one of claims 1 to 6 in the preparation of insulating flame-retardant plastic products.
Citation Information
Patent Citations
Flame-retardant polypropylene material and preparation method thereof
CN114410010A
Polyphenylene sulfide composite material with high CTI performance and preparation method thereof
CN115895261A
Cited By
Metal and metal-based composite new material preparation process
CN120382159A